1976
DOI: 10.1002/app.1976.070200108
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting dynamic durability of polycarbonate under bending, torsional, and impacting fatigue and in cavitation erosion and dynamic solvent cracking conditions

Abstract: SynopsisTo understand influences of various factors on dynamic durability of engineering plastics, effects of average molecular weights of samples, molding variables, preparing methods of specimens, and fillers on plane and rotational bending, torsional, and impacting fatigue and cavitation erosion and solvent cracking of polycarbonate were studied. From the experimental results, the following tendencies are observed as a whole in case of polycarbonate: The extent of influence of the factors on dynamic durabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…reaches a value somewhere between 100,000 and 200,000. While this may be true for some properties, such as Tg or possibly modulus, it does not hold for ultimate properties such as fatigue endurance [14,15,[74][75][76]. Also, various literature references indicate that increasing molecular weight also increases craze strength, creep resistance, and endurance under long-time steady loading [3,77].…”
Section: B Molecular Weightmentioning
confidence: 89%
“…reaches a value somewhere between 100,000 and 200,000. While this may be true for some properties, such as Tg or possibly modulus, it does not hold for ultimate properties such as fatigue endurance [14,15,[74][75][76]. Also, various literature references indicate that increasing molecular weight also increases craze strength, creep resistance, and endurance under long-time steady loading [3,77].…”
Section: B Molecular Weightmentioning
confidence: 89%
“…It was also proposed that the incorporation of a plasticizing comonomer n-butyl-acrylate resulted in complex FCP behavior. Various methods are used to test fatigue life, several of which were either developed or improved upon by Ohishi, et al (102). Their bending fatigue tests on PC showed that the effect of MW was irregular.…”
Section: Polymer Engineeringmentioning
confidence: 99%
“…For torsional properties, Ohishi, et al (102), developed a new testing apparatus called "MO-U". The apparatus is capable of measuring torsional fatigue strength under constant amplitude of deformation and static torsional properties.…”
Section: Polymer Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhateja et al4 studied the response of an ultrahigh molecular weight linear polyethylene under a low cycle (<20), repeated the impacting of notched samples under three‐point bending. Ohishi et al5 studied unnotched polycarbonate under a repeated drop weight with a three‐point bending apparatus and produced a curve of the applied stress versus the number of cycles to failure. Sacher et al6 examined the effect of repeated impacts on polymer surfaces in terms of heat generation and mechanochemical reactions.…”
Section: Introductionmentioning
confidence: 99%